Early life irradiation-induced hypoplasia and impairment of neurogenesis in the dentate gyrus and adult depression are mediated by microrna-34a-5p/t-cell intracytoplasmic antigen-1 pathway - Wang, H (MDPI AG, 2021)
10.3390/cells10092476